2004
DOI: 10.1128/aem.70.12.7200-7209.2004
|View full text |Cite
|
Sign up to set email alerts
|

Bile-Mediated Aminoglycoside Sensitivity in Lactobacillus Species Likely Results from Increased Membrane Permeability Attributable to Cholic Acid

Abstract: Few studies have been conducted on antimicrobial resistance in lactobacilli, presumably because of their nonpathogenic nature as anaerobic commensals. We assessed resistance in 43 type strains and isolates representing 14 species by using agar disk diffusion and MIC analysis in MRS medium. Most noteworthy were two general phenotypes displayed by nearly every strain tested: (i) they were more susceptible (up to 256-fold in some cases) to the deconjugated bile acid cholic acid than to the conjugate taurocholic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
35
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 43 publications
7
35
0
Order By: Relevance
“…In addition, it was shown that when lactobacilli were grown in medium containing bile, they became more sensitive to aminoglycosides, suggesting that membrane impermeability plays an important role in this intrinsic aminoglycoside resistance (9). Our results also showed that the LAB are intrinsically resistant when the SCAN or FEEDAP MIC breakpoints are used (Table 4).…”
Section: Discussionsupporting
confidence: 69%
“…In addition, it was shown that when lactobacilli were grown in medium containing bile, they became more sensitive to aminoglycosides, suggesting that membrane impermeability plays an important role in this intrinsic aminoglycoside resistance (9). Our results also showed that the LAB are intrinsically resistant when the SCAN or FEEDAP MIC breakpoints are used (Table 4).…”
Section: Discussionsupporting
confidence: 69%
“…S2), we proceeded to test the MIC of gentamicin, streptomycin, neomycin and kanamycin in the presence of 1 mM SC. The MIC of all aminoglycosides was reduced in the presence of 1 mM SC (Table 3), consistent with a previous study in Lactobacillus species (Elkins & Mullis, 2004), where the authors implicated increased antibiotic uptake following bile exposure.…”
Section: Development Of a Bursa Aurealis Transposon Mutagenesis Screesupporting
confidence: 80%
“…As with bile acids, reports of bacterial interactions with steroid hormones are limited to the hydrolysis of such conjugates (deconjugation) and transformations of the steroid ring structure by several genera of gram-positive commensal bacteria (2). The significance of these activities to the bacterium remains unclear but may involve sequestering substrates for assimilatory or metabolic pathways (22) or providing a mechanism to modulate membrane permeability (4). Thus far, these activities have been attributed to a gram-negative organism in only a few cases, which, interestingly, implicated E. coli in the hydrolysis of steroid glucuronides (8) and the 7␣-dehydroxylation of bile acids (23).…”
mentioning
confidence: 99%
“…3). Thus, estradiol uptake was monitored at increasing concentrations of either conjugated (taurocholic) or deconjugated (cholic) bile acid within GI tract physiological ranges of Ͻ10 mg/ml (approximately 18 to 20 mM) supplied exogenously in the assay medium during the preincubation period of the (4). Exogenous hydrocortisone, like exogenous taurocholic and cholic acids, failed to significantly modulate estradiol uptake, unlike exogenous progesterone, which provided the largest modulation and produced a biphasic profile.…”
mentioning
confidence: 99%
See 1 more Smart Citation